2003
DOI: 10.4141/s02-017
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of liquid hog manure on the phosphorus status of a silt loam cropped to corn

Abstract: . 2003. Long-term effects of liquid hog manure on the phosphorus status of a silt loam cropped to corn. Can. J. Soil Sci. 83: 589-600. Repeated application of animal manure or mineral P fertilizer can significantly increase soil P content and enhance the risk of water contamination. The objectives of this study were to evaluate the long-term (8 yr) effect of liquid hog manure (LHM) applied at high rates and its timing of application on the soil P status and on the risk index of water contamination by P. Spring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Similarly, the amount of phosphorus extractable in water appears to have been influenced by manure additions. Royer et al (2003) have reported similar results after 8 years of liquid hog manure application to a silt loam soil. The high amount found in the subsoil of the control relative to the topsoil may be attributed to its finer texture that might have delayed leaching towards the deeper layers.…”
Section: Discussionsupporting
confidence: 79%
“…Similarly, the amount of phosphorus extractable in water appears to have been influenced by manure additions. Royer et al (2003) have reported similar results after 8 years of liquid hog manure application to a silt loam soil. The high amount found in the subsoil of the control relative to the topsoil may be attributed to its finer texture that might have delayed leaching towards the deeper layers.…”
Section: Discussionsupporting
confidence: 79%
“…Unlike synthetic N fertilizers, legumes utilized as GM represent a potentially renewable source of on‐farm, biologically fixed N and may also fix and add large amounts of C to cropping systems (Hargrove, 1986; Sharma and Mittra, 1988). Providing adequate soil N fertility with application of animal manure products may result in soil P loading (because manure N/P ratios are often much lower than those maintained by plants; Royer et al, 2003; Hao et al, 2004) or soil salinization (due to high ion concentrations in animal manure; Hao and Chang, 2003). Such excess P application and soil salinization may be avoided by use of leguminous GMs (Eigenberg et al, 2002).…”
Section: Review Of Green Manure Studies: Tropical Legumes and Nonlegumentioning
confidence: 99%
“…The enhanced level of POM-C, however, could also be related to infiltration of LSM into the soil profile when applied at the high rate (Bakhsh et al 2001;Elmi et al 2005). In this regard, even nutrients of low mobility such as P could pose a risk of movement to drainage waters with repeated LSM application at high rates (Royer et al 2003).…”
Section: Residual Treatment Effect On Soil C and N Parametersmentioning
confidence: 99%